Design and Development of an Android-Based Laundry Application with a Drop-and-Go System - Abdillah Fa'iz; Muhamad Fikri (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Manual administration in MSME laundry businesses is a primary source of operational inefficiency, generating service bottlenecks and a high risk of human error. High-mobility customers are hindered by slow manual record-keeping, the absence of order status transparency, and the lack of digital payment options. This study aims to design and develop an Android-based laundry application incorporating a Drop and Go system to fully automate and eliminate these administrative barriers. The system integrates a self-service booking feature, QR Code scanning for instant drop-off confirmation, and the Midtrans payment gateway for cashless transactions. The application was developed using the Flutter framework and Node.js, following the Waterfall methodology. Black-box testing on 10 Customer Application scenarios and 14 Outlet Application scenarios yielded a successful status for all functionalities. System Usability Scale (SUS) evaluation produced an average score of 75 (Good) for the Customer Application and 85 (Excellent) for the Outlet Application, demonstrating that the system is viable for implementation as a modernization solution for MSME laundry operations.